Agronomy - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
The results of regional trials for promising cassava var. under uniform improved technology are given. Trials were conducted in Media Luna, Chigorodo, Carimagua, Rio Negro, San Martin, CIAT- Palmira, CIAT-Quilichao, and Caicedonia. In 7 of the 8 sites, var. M COL 1684, CM 342-55, and CM 489-1 outyielded the best local clones. Var. M COL 1468, M COL 1684, and M COL 22 tested over 45, 40, and 40 cycles, resp. have produced weighted av. yields of 29.1, 30.8, and 22.0 t/ha, resp. Yields of the 1st 2 are both high and relatively stable while yields of M COL 22 are lower and unstable. The Centro Internacional de Agricultura Tropical tested and simplified the single leaf-bud cutting technique for the international transfer of cassava var. in a joint project with Philippine workers. Trials were conducted on chemical weed control in cassava in monoculture and in mixed cropping systems. The response to N-P-K fertilization in cowpea/cassava intercrops was determined. Studies were conducted to determine the effect of chemical treatments and storage duration of cuttings on germination, early growth, and canopy formation. (CIAT)